2023
DOI: 10.1108/imr-12-2021-0372
|View full text |Cite
|
Sign up to set email alerts
|

International relationship management during social distancing: the role of AI-integrated social CRM by MNEs during the Covid-19 pandemic

Abstract: PurposeThe research empirically examines the role of artificial intelligence (AI) integrated with social customer relationship management (SCRM) in multinational enterprises (MNEs) towards international relationship management under social distancing conditions due to the COVID-19 pandemic.Design/methodology/approachThe study initially undertakes pertinently focused theoretical research in the fields of international marketing, knowledge management, and customer relationship management. And, utilizing the theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…Configuring an AI‐integrated customer relationship capability and combining it with global customer support, automation, and knowledge management improves firm performance in international marketing (Chatterjee et al, 2023). As an example of knowledge management, managers can use AI in a two‐layered inductive learning procedure where two different modules assess international financial risk in internationalization (Tessmer et al, 1993).…”
Section: Managing Ai In Ib: Empirical Insights and Toward A Research ...mentioning
confidence: 99%
“…Configuring an AI‐integrated customer relationship capability and combining it with global customer support, automation, and knowledge management improves firm performance in international marketing (Chatterjee et al, 2023). As an example of knowledge management, managers can use AI in a two‐layered inductive learning procedure where two different modules assess international financial risk in internationalization (Tessmer et al, 1993).…”
Section: Managing Ai In Ib: Empirical Insights and Toward A Research ...mentioning
confidence: 99%
“…AI-CRM is recognized as a transformative technology that can significantly impact an organization's integration capability. Integration capability refers to the ability of an organization to seamlessly merge and utilize different technological components (Chatterjee et al, 2023). Studies have indicated that AI-CRM systems, with their ability to centralize customer data and automate processes, play a crucial role in enhancing integration across various organizational functions (Alokla et al, 2019;Chatterjee et al, 2023;Liu et al, 2013).…”
Section: A Ai-crm Adoptionmentioning
confidence: 99%
“…Integration capability refers to the ability of an organization to seamlessly merge and utilize different technological components (Chatterjee et al, 2023). Studies have indicated that AI-CRM systems, with their ability to centralize customer data and automate processes, play a crucial role in enhancing integration across various organizational functions (Alokla et al, 2019;Chatterjee et al, 2023;Liu et al, 2013). The integration of AI-CRM tools enables a more cohesive and holistic approach to customer relationship management, contributing to overall organizational efficiency (Ledro et al, 2022).…”
Section: A Ai-crm Adoptionmentioning
confidence: 99%
See 2 more Smart Citations